Martin Luther as Comforter - Leroux, Neil (BRILL, 2007)
Using meticulous rhetorical analysis of several important Luther texts, this book examines how he offers comfort to those who are facing their own death or who are coming to terms with the death of loved ones.
Description based on publisher supplied metadata and other sources
Keywords: Luther; Martin; Tod; Trost